SEPATU UNTUK MENCEGAH LUKA PADA KAKI PENDERITA DIABETES - Laksono, Muhamad Galih Tri; Hapsari, Indah Fitriana (Anggada : Jurnal Desain dan Seni, 2020)
The foot is a part of an animal or human body that is used for walking. Diabetes is a long-lasting or chronic disease characterized by high blood sugar (glucose) levels or above-average values. Glucose, which accumulates in the blood due to not being absorbed by body cells properly, can cause various disorders of the body’s organs. In people with diabetes, the leg is a part of the body that is vulnerable to injury. When a person with diabetes has a wound on his body, the damage is difficult to heal. So it needs special handling. After conducting previous research, the author found several deficiencies in diabetic shoes already on the market. Thus the authors make shoes in which these shoes are designed by prioritizing research on aspects that are lacking and still not found in diabetic shoes already on the market.